If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -1x + 8 = 7 Reorder the terms: 8 + 2x + -1x = 7 Combine like terms: 2x + -1x = 1x 8 + 1x = 7 Solving 8 + 1x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = 7 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 7 + -8 1x = 7 + -8 Combine like terms: 7 + -8 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| y=ax^2-b | | 3c^2-8c+4=0 | | x^2-8y+6x+25+y^2=0 | | 4=3x-18 | | 66-(7x+6)=7(x+2)+x | | 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 |